POLA LINGKARAN PERTUMBUHAN OTOLITH IKAN GABUS (Channa Striata) DI PERAIRAN SUNGAI SIAK PROVINSI RIAU - Ridwan Manda Putra (Berkala Perikanan Terubuk, 2009)
This research was conducted from July to September 2008. It was aimedto understand the growth rings pattern in the otolith of Channa striata. Thirthyfour fishes were collected with variations sizes. Growth rings pattern in the otolithwas studied by shaving the otolith, following methods described by Windarti(2007). The number of rings were counted and their pattern were described.Results shown that growth ring pattern in the otolith is varied, the ringsare consisted of thick and thin rings. Many fishes have several thick rings aroundthe nucleus of the otolith, while few fishes have thin rings around the nucleus.These data shown that many fishes faced growth related problems when they areyoung as it is indicated by the presence of thick rings around the nucleus. It ispredicted that small/young fish may not be able to tolerate water quality changingdue to the presence of pollutant.